2022
DOI: 10.3390/ijms231911434
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/β-Catenin Signaling Pathway Is Strongly Implicated in Cadmium-Induced Developmental Neurotoxicity and Neuroinflammation: Clues from Zebrafish Neurobehavior and In Vivo Neuroimaging

Abstract: Cadmium (Cd) is a toxic heavy metal and worldwide environmental pollutant which seriously threatens human health and ecosystems. It is easy to be adsorbed and deposited in organisms, exerting adverse effects on various organs including the brain. In a very recent study, making full use of a zebrafish model in both high-throughput behavioral tracking and live neuroimaging, we explored the potential developmental neurotoxicity of Cd2+ at environmentally relevant levels and identified multiple connections between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 77 publications
1
8
0
Order By: Relevance
“…Our results showed that the phosphorylation of NF-κB was significantly reduced ( Figure 5 a–c), while the baseline level of proteins was unaffected. Moreover, the expression of iNOS expression in microglia mainly depends on the activation of ERK1/2 [ 19 ]. Our results further showed that the phosphorylation of ERK1/2 was decreased in Wnt3a-overexpressed BV-2 cells ( Figure 5 d–f).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the phosphorylation of NF-κB was significantly reduced ( Figure 5 a–c), while the baseline level of proteins was unaffected. Moreover, the expression of iNOS expression in microglia mainly depends on the activation of ERK1/2 [ 19 ]. Our results further showed that the phosphorylation of ERK1/2 was decreased in Wnt3a-overexpressed BV-2 cells ( Figure 5 d–f).…”
Section: Resultsmentioning
confidence: 99%
“…The Wnt/β-catenin signaling pathway is crucial in maintaining neuronal homeostasis [ 18 ]. It has been reported that activation of the Wnt/β-catenin signaling pathway can inhibit pathological neuroinflammation [ 17 , 19 ]. In addition, the Wnt/β-catenin signaling pathway is involved in anti-tumor immunity, in which β-catenin can regulate NF-κB activation [ 17 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…A complex combination of genetic factors, life events, and lifestyles triggers these pathological processes. Mental triggers include traumatic events, depression ( Gu et al, 2022 ), physical stressors such as radiotherapy ( Gu et al, 2022 ; Gutierrez-Quintana et al, 2022 ), traumatic brain injury, viral or bacterial infections ( Akinci et al, 2022 ; Francis et al, 2023 ), and exposure to toxins such as toxic heavy metals ( Mani et al, 2022 ; Xu et al, 2022 ), insecticides, chemotherapy agents, medicaments, and a fatty diet. A recent study showed that neuroinflammation could also be associated with epigenetic changes induced by Posttraumatic Stress Disorder (PTSD) ( Wolf et al, 2018 ) (see Figure 1 ).…”
Section: Memory Loss During Agingmentioning
confidence: 99%
“…The impact of the neurotoxic agent can also be evaluated by analysing the expression of genes associated with neuronal development and differentiation ( Supplementary Table S2 ). These genes encompass immature neuronal markers like nestin ( Chen et al, 2012 ; Ho et al, 2013 ; Soares et al, 2017 ; Qian et al, 2018 ; Cheng et al, 2020 ; Xia et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ; Yu et al, 2022 ; Xu et al, 2023 ), as well as mature neuronal markers like growth associated protein 43 ( gap43 ) ( Chen et al, 2012 ; Sun et al, 2016 ; Soares et al, 2017 ; Faria et al, 2018 ; Qian et al, 2018 ; Shi et al, 2018 ; Jin et al, 2019b ; Li et al, 2019 ; Cheng et al, 2020 ; Zhu et al, 2020 ; Chen et al, 2021 ; Gyimah et al, 2021 ; Li et al, 2021 ; Tian et al, 2021 ; Xu et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ; Yu et al, 2022 ; Shi et al, 2023 ; Xiong et al, 2023 ; Xu et al, 2023 ; Zhu et al, 2023 ), and elav like RNA binding protein 3 ( elavl3 ) ( Chen et al, 2012 ; Sun et al, 2016 ; Qian et al, 2018 ; Shi et al, 2018 ; Yang et al, 2019 ; Zhu et al, 2020 ; Chen et al, 2021 ; Gyimah et al, 2021 ; Wang et al, 2021 ; Xu et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ; Fan et al, 2022 ; Wang et al, 2022 ; Yu et al, 2022 ; Xiong et al, 2023 ; Zhu et al, 2023 ). Additionally, astrocyte markers such as glial fibrillary acidic protein ( gfap ) ( Chen et al, 2012 ; Sun et al, 2016 ; Soares et al, 2017 ; ...…”
Section: Neurotoxic Effect On Embryonic Developmentmentioning
confidence: 99%
“…Gene expression analysis related to axons has demonstrated alteration in the expression of regeneration-associated genes such as growth-associated protein Gap-43 ( gap43 ) ( Chen et al, 2012 ; Sun et al, 2016 ; Soares et al, 2017 ; Faria et al, 2018 ; Qian et al, 2018 ; Shi et al, 2018 ; Jin et al, 2019b ; Li et al, 2019 ; Cheng et al, 2020 ; Zhu et al, 2020 ; Chen et al, 2021 ; Gyimah et al, 2021 ; Li et al, 2021 ; Tian et al, 2021 ; Xu et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ; Chang et al, 2022 ; Yu et al, 2022 ; Shi et al, 2023 ; Xiong et al, 2023 ; Xu et al, 2023 ; Zhu et al, 2023 ) and α1 tubulin ( Sun et al, 2016 ; Li et al, 2018 ; Shi et al, 2018 ; Yang et al, 2019 ; Fu et al, 2020 ; Zhu et al, 2020 ; Chen et al, 2021 ; Gyimah et al, 2021 ; Xu et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ; Heredia-García et al, 2023 ; Shi et al, 2023 ; Xu et al, 2023 ). Additionally, nerve related genes like pax6a ( Ho et al, 2013 ; Li et al, 2019 ; Wang et al, 2021 ; Gyimah et al, 2022 ), elavl3 ( Chen et al, 2012 ; Sun et al, 2016 ; Qian et al, 2018 ; Shi et al, 2018 ; Yang et al, 2019 ; Zhu et al, 2020 ; Chen et al, 2021 ; Gyimah et al, 2021 ; Wang et al, 2021 ; Xu et al, 2021 ; Xu et al, 2022a ; Xu et al, 2022b ; Fan et al, 2022 ; Wang et al, 2022 ; Yu et al, 2022 ;…”
Section: Morphology and Characteristics Of Neuronsmentioning
confidence: 99%